Filologia Brunona Schulza. O tożsamości „na styku kultur” .......... 163 - Kołodziej, Piotr (Tożsamość na styku kultur: 4, 2021)
PHILOLOGY OF BRUNO SCHULZ. IDENTITY AT THE INTERSECTION OF CULTURESThis text concerns “philology” of Bruno Schulz. The author of The Cinnamon Shops regards philology as “a deep, creative research of the word” and as the equivalent of the term “philosophy.” The philosophy/philology, which Schulz discussed in his essay The Mythologization of Reality, was put into practice by the writer through creating oneiric narrations deeply rooted in mythological and symbolical structures with the aim of “mythologization,” that is, “giving sense” and making one’s own individual fate universal. Schulz moves across various cultural registers, penetrates and, at the same time, creates his own identity “at the intersection of times” and “at the intersection of cultures.” The attitude of the writer as well as the legitimacy of his artistic actions are analyzed in terms of various contexts (e.g. parts of texts by S. Freud, C.G. Jung, M. Eliade, E. Cassirer, E. Fromm, and O. Sacks; works of art by J. Vermeer, and S. Dalí). The author also explains why he chose these contexts and how they could be implemented into the area of reading.